Computational methods and clinical applications for spine imaging : 4th international workshop and challenge, CSI 2016 : held in conjunction with MICCAI 2016 Athens, Greece, October 17, 2016 ; revised selected papers /: 4th international workshop and challenge, CSI 2016 : held in conjunction with MICCAI 2016 Athens, Greece, October 17, 2016 ; revised selected papers. ([2016]) - Unknown
No abstract available